Suzuki–Miyaura Coupling Based Enantioselective Synthesis of (+)-epi- Clausenamide and the Enantiomer of Its 3-Deoxy Analogue - Zhang, Lu; Zhou, Yumei; Yu, Xiaoming (Synlett, 2012)
The first enantioselective synthesis of two biologically interesting close analogues of clausenamide, namely (+)-epi-clausenamide and (–)-3-deoxy-epi-clausenamide, was reported. Key steps of the synthesis included construction of the chiral pyrrolinone intermediates from d- and l-serine derivatives, introduction of the C4-phenyl by Suzuki–Miyaura coupling and establishment of the C6 configuration by a threo-selective Grignard reaction. Optimization of the key Suzuki–Miyaura coupling reaction was described in detail.
Keywords: (+)-epi-clausenamide; (–)-3-deoxy-epi-clausenamide; nootropics; osteoporosis; Suzuki–Miyaura coupling